Incidence of football injuries in youth players. Comparison of players from two European regions - Junge, A.; Chomiak, J.; Dvorak, J. (The American Journal of Sports Medicine, 2000)
Several authors have investigated the frequency of football injuries in youth players. However, the results of these studies are inconsistent because of the different age groups investigated and the different methods applied. The aim of the present study was to compare the incidence and characteristics of football injuries in youth players of two European regions. A total of 444 youth players from the Czech Republic and the Alsace region of France and Germany were followed weekly for 1 year. In 311 players (70%), complete weekly follow-ups over the 1-year period were available. The comparison of injury data revealed no substantial differences between players from the Alsace region and the Czech Republic in injury incidence per 1000 hours of exposure, degree of injury severity, or the circumstances in which the injuries occurred. However, players from the Czech Republic spent more time in training and playing football than did players from the Alsace region, and in the Czech Republic a higher proportion of injuries was caused by foul play. With only a few exceptions, the statistics were similar in the amount of football played as well as in the incidence of injury between different age and skill levels in both European regions.